Regional convergence and human capital in Mexico, from the 80s to 2002 - Barceinas, Fernando; Raymond, José Luis (Estudios Económicos de El Colegio de México, 2005)
The paper analyzes the problems of regional convergence for the Mexican case. Although some mechanisms of regional convergence operate, for instance those related to the greater performance of educational investment in less developed regions before those more developed, the available evidence suggests that in the economy a process of divergence has operated. Certain externalities inherent to economic development, strengthened by liberalization and globalization are identified as possible causes of the process.